The drifting city: The role of affect and repair in the development of "Enabling Environments" - Duff, Cameron (Elsevier BV, 2009)
Background: The city has become a defining feature of contemporary human experience, supporting diverse risk and enabling environments. Whilst urban risk environments have been the subject of numerous innovative research projects in recent years, the figure of the enabling environment is less well understood. This paper seeks to develop this figure through reference to recent scholarship in social theory, human geography and urban sociology. Methods: This figure will be illustrated throughout with data drawn from various qualitative research projects conducted in Melbourne, Australia and Vancouver, Canada. This qualitative research highlights the array of enabling characteristics present in urban drug use contexts, characteristics that have yet to be fully explored in relation to the development of innovative settings-based harm reduction strategies. Results: This research draws attention to the ways particular urban settings support the development of affective and relational networks of "social repair" vital to the maintenance of health and wellbeing. These enabling characteristics serve to build social ties and enhance local networks; increase belonging and "connection to place"; and reinforce local "cultures of care". They also represent resources of enormous potential for harm reduction policy and practice. Conclusions: Greater attention to the array of assets and opportunities present in urban settings offers fresh insights into the nature of enabling environments and their role in reducing drug related harms and facilitating healthy growth and development. © 2008 Elsevier B.V. All rights reserved.